2007
DOI: 10.1016/j.jacc.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

T-Wave Alternans, Restitution of Human Action Potential Duration, and Outcome

Abstract: The mechanism by which TWA predicts arrhythmic mortality does not reflect the maximum slope of ventricular APD restitution. Better understanding of the mechanisms underlying TWA may enable improved prediction and prevention of ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 29 publications
12
73
1
Order By: Relevance
“…Thus, APD restitution likely does not explain alternans at this rate. This result has also been confirmed in patients with steep maximum APD restitution at short diastolic intervals (14). …”
Section: Discussionsupporting
confidence: 53%
“…Thus, APD restitution likely does not explain alternans at this rate. This result has also been confirmed in patients with steep maximum APD restitution at short diastolic intervals (14). …”
Section: Discussionsupporting
confidence: 53%
“…Until the last decade, it was believed that a steep action potential duration (APD) restitution (>1) at rapid heart rates (Weiss et al, 2006) produces alternans in APD that underlie T-wave alternans and the genesis of fibrillation (Pastore et al, 1999). However, MTWA is most successful in stratifying risk in patients at near-resting heart rates < 110 bpm, where APD restitution is flat (Narayan et al, 2007). Computational models of the LV wall in combination with clinical data revealed that abnormal handing of intracellular calcium underlies alternans in action potential voltage (APV-ALT), defined as the oscillation of the plateau voltage of the action potential, which results in MTWA at moderate heart rates, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, research has reported a strong correlation between increased arrhythmia risk and the presence of microvolt T-wave alternans (MTWA) [26,58]. However, the mechanistic basis of MTWA preceding lethal ventricular arrhythmias has been under debate since MTWA is most successful in stratifying risk in patients at heart rates < 110 bpm, where APD restitution is flat [86]. Computational models of the left ventricular (LV) wall in combination with clinical data revealed that abnormal intracellular calcium handling underlies alternans in action potential voltage, which result in MTWA at heart rates < 110 bpm [17,85]; abnormalities in intracellular calcium have long been linked to ventricular fibrillation [80,129].…”
Section: Modeling To Identify Individuals With a High Risk Of Developmentioning
confidence: 99%